2018
DOI: 10.1016/j.eurpsy.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting time to recall in patients conditionally released from a secure forensic hospital: A survival analysis

Abstract: Time to recall can be predicted by a range of factors that are readily available to clinical teams. Further research is required to determine if targeted interventions can modify the likelihood or time to recall for conditionally released forensic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A literature search of existing research on recall identified only four studies: Riordan et al (2006), O'Sullivan et al (2013), Chiringa et al (2014) and Jewell et al (2018). Findings from these studies have helped to identify the factors that can contribute to the likelihood of FSUs being recalled, including lack of social support, substance misuse and a history of mental health issues prior to the index admission.…”
Section: Introductionmentioning
confidence: 99%
“…A literature search of existing research on recall identified only four studies: Riordan et al (2006), O'Sullivan et al (2013), Chiringa et al (2014) and Jewell et al (2018). Findings from these studies have helped to identify the factors that can contribute to the likelihood of FSUs being recalled, including lack of social support, substance misuse and a history of mental health issues prior to the index admission.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one can interpret this in favor of the Safe pilot group because even if the matched controls had a potentially more efficient violence prevention measure due to their medication, the Safe pilot-patients were only involved in about 10% of the violent episodes. Other research has found that pharmaceutical treatment has reduced the risk of being returned to a forensic hospital (e.g 21…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with a shorter time until recalled were younger age, non-white ethnicity, history of substance abuse, early childhood maladjustment, depot medication, and having been known to mental health services. Remarkably, treatment with clozapine reduced the risk of recall ( Jewell et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%